Language test development a practical guidebook / Ahmad Daud Ibrahim ... [et al.] - Ibrahim, Ahmad Daud; Muhammad, Ahmad Mazli; Mohd Kasim, Aini Akmar; Ahmad Shah, Baizura; Omar, Megawati; Abdul Manan, Norleza; Mohamed Noor, Roseleena (Academy of Language Studies, 2018)
This guidebook intends to assist language educators in understanding and internalising the rigours of assessment. Based on best practices of test construction and vetting processes that language test developers at Akademi Pengajian Bahasa (APB), Universiti Teknologi MARA (UiTM) accumulated over two decades, this book is conveniently divided into seven topics that cover all four essential skills (reading, writing, listening and speaking) in language learning and teaching: 1.0 Introduction, 2.0 General Points to Consider When Setting a Test Paper, 3.0 Guidelines in the Construction of Grammar Tests, 4.0 Guidelines in the Construction of Reading Tests, 5.0 Guidelines in the Construction of Writing Tests, 6.0 Guidelines in the Construction of Listening Tests, and 7.0 Guidelines in the Construction of Speaking Tests. A comprehensive presentation of information that includes examples of papers is adopted so that the intricacy and conundrum of language test development can be easily comprehended and implemented. The authors hope that this guidebook can provide language educators with valuable insights that contribute towards the strengthening of language assessment practices in many years to come.